2018
DOI: 10.1111/nep.13448
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying cognitive dysfunction across the spectrum of end‐stage kidney disease: A systematic review and meta‐analysis

Abstract: Cognitive dysfunction is reportedly highly prevalent among chronic kidney disease (CKD) patients. A variety of screening tools and neuropsychiatric batteries are used to quantify the magnitude and nature of this dysfunction. Our objective is to summarize the neurocognitive testing used, and determine what degree cognitive dysfunction is reported in CKD patients. All study designs published in English that contained participants who were either pre‐dialysis patients, haemodialysis (HD) or peritoneal dialysis (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
2
25
1
1
Order By: Relevance
“…There are several studies investigating cognitive performance across the CKD spectrum, i.e., pre-dialysis CKD patients, patients on renal replacement therapy (hemodialysis or peritoneal dialysis), and transplant recipients for a systematic review, see (Vanderlinden et al, 2019). A recent meta-analysis found that ESRD patients submitted to different modalities of renal replacement therapy have distinct cognitive deficits.…”
Section: Cognitive Impairment In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies investigating cognitive performance across the CKD spectrum, i.e., pre-dialysis CKD patients, patients on renal replacement therapy (hemodialysis or peritoneal dialysis), and transplant recipients for a systematic review, see (Vanderlinden et al, 2019). A recent meta-analysis found that ESRD patients submitted to different modalities of renal replacement therapy have distinct cognitive deficits.…”
Section: Cognitive Impairment In Ckdmentioning
confidence: 99%
“…Both pre-dialysis and patients on hemodialysis exhibited worse global cognition performance in comparison with non-CKD controls, as demonstrated by the significantly lower scores on the Mini-Mental State Examination. Also, patients on peritoneal dialysis or hemodialysis had worse attention/working memory performance, as evaluated by the Trail Making Test-A, than non-CKD controls (Vanderlinden et al, 2019).…”
Section: Cognitive Impairment In Ckdmentioning
confidence: 99%
“…However, no major neurocognitive deficits was observed in mild to moderate CKD patients, with eGFR of 30 to 90 ml/mn/ 1.73 m 2 [47,48]. Predialysis patients and dialysis patients are likely to exhibit cognitive impairment [55,56]. Verbal, Performance and Full Score IQs of patients with ESRD (eGFR< 18 ml/mn/1.73m 2 ) were significantly lower than the IQs of sibling controls [57].…”
Section: Discussionmentioning
confidence: 99%
“…[17,26] Therefore, Vanderlinden et al thought that the cut-off scores on dementia screening tools such as the 3MS and MMSE may not be sensitive enough to detect impairment in these populations. [23] Meanwhile, TMT-B test was also commonly used in the studies included. Compared to TMT-A test, the TMT-B adds additional executive cognitive load via mental shifting.…”
Section: Discussionmentioning
confidence: 99%
“…[21] However, the studies with respect to different dialysis modalities are both too scarce and insufficient to allow for modality-specific conclusions. Although there were several meta-analyses concerning this topic, [2,22,23] the studies included are not up-to-date and not comprehensive. In this systematic review and meta-analysis, we collected all the studies comparing the cognitive functions between HD and PD, concluding that PD might be superior in preserving the cognitive functions and decreasing the risk of dementia compared with HD.…”
Section: Introductionmentioning
confidence: 99%